Highly efficient micro-meso acidic H-USY catalyst for one step conversion of wheat straw to ethyl levulinate (biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Mudliar, Sandeep; Bokade, Vijay (Microporous and Mesoporous Materials, 2020)
Ethyl Levulinate (EL), biofuel additive can blend up to 20% with biodiesel to improve its fuel properties. Till the date, there are reports on homogeneous catalysts (H2SO4, ionic liquid) for synthesis of EL from raw biomass like wheat straw. To best of our knowledge, there is no single report on heterogeneous catalyst for one step synthesis of EL directly from wheat straw. This work is a successful attempt to use heterogeneous micro-meso acidic H-USY (post dealumination and desilication) for direct one step conversion of wheat straw to EL with higher EL yield 24.5 wt%, which is probably the highest so far.
Keywords: Acidity; ethyl levulinate; H-USY; Micro-meso; Wheat straw

Effect of acidity and mesoporosity in H-USY on conversion of wheat straw to ethyl levulinate (Biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Nandanwar, Sachin; Bokade, Vijay (Journal of the Indian Chemical Society, 2023)
Cold flow properties of biodiesel can be improved by addition of additives especially ethyl levulinate (EL up to 20%). There are very limited information on synthesis of EL from actual raw biomass like wheat straw over heterogeneous catalyst. The present article elaborated on optimization of Acidity to Mesoporosity ratio in H-USY, which is crucial for its application in conversion of raw wheat straw to selective formation of EL in one-step. The acidity and mesoporosity is monitor by systematic post treatment of desilication and dealumination. Optimum acidity/mesoporosity ratio of 3.6 in HUSY resulted in to maximum EL yield of 24.5%, which is probably the highest so far.
Keywords: Acidity; Biofuel additive; Dealumination; Desilication; ethyl levulinate; H-USY; Mesoporosity; Wheat straw

Lignocellulosic biomass analysis: acidic lignin recovery, characterisation, and depolymerisation - Singh, Sandip K.; Matsagar, Babasaheb M.; Dhepe, Paresh L. (Biomass Conversion and Biorefinery, 2024)
For the development of an effective lignocellulosic biomass conversion technology to biofuels and chemicals, the biomass composition analysis and their properties need to be characterised prior to biomass valorisation, including polysaccharide hydrolysis and lignin depolymerisation. In this work, a facile colorimetric titration method for the quantification of alpha-, beta-, and gamma-cellulose, pentosan, lignin, and silica percentages of wheat straw (WS) and two bagasse (BG I and II) samples was done. The result showed higher amounts of structural biopolymers (i.e. holocellulose and lignin (similar to 89.3%)) in BG compared to WS (81%) sample. Lignin recovery from BG (I and II) and WS samples was done by applying two-stage concentrated and dilute sulphuric acid hydrolysis, and maximum recovery (i.e. 21.5%; acid soluble +insoluble) of lignin obtained from BG II sample. Elemental and composition analysis results were represented substantial differences in lignin properties, including higher heat values (19.8 MJkg(-1)) of recovered lignin from BG II as well as high amounts of silica percentage from WS lignin. An intense Si-O-Si asymmetric stretching mode and/or C-O-C aliphatic aromatic ether (similar to 1100 cm(-1)) was characterised for lignin derived from WS. C-13 CP-MAS NMR exhibited variable intensities for dibenzodioxocin, spirodienone, and tricin moieties in recovered lignin samples. These lignin samples were processed for depolymerisation using homogeneous (1-methyl-3-(3-sulphopropyl)-imidazolium hydrogen sulphate) and heterogeneous (immobilised Bronsted acidic ionic liquid) catalysts to lower molar mass aromatic fractions and represented 89% and 92% organic solvent-soluble product yields respectively from WS-derived lignin.
Keywords: bagasse; Dibenzodioxocin; Holocellulose; Lignin depolymerisation; Spirodienone; Tricin; Wheat straw